2010
DOI: 10.1101/gad.605910
|View full text |Cite
|
Sign up to set email alerts
|

Rec8-containing cohesin maintains bivalents without turnover during the growing phase of mouse oocytes

Abstract: During female meiosis, bivalent chromosomes are thought to be held together from birth until ovulation by sister chromatid cohesion mediated by cohesin complexes whose ring structure depends on kleisin subunits, either Rec8 or Scc1. Because cohesion is established at DNA replication in the embryo, its maintenance for such a long time may require cohesin turnover. To address whether Rec8-or Scc1-containing cohesin holds bivalents together and whether it turns over, we created mice whose kleisin subunits can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
269
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(280 citation statements)
references
References 60 publications
9
269
1
1
Order By: Relevance
“…It is reported that the expression of oocyte genes that are related to cell cycle regulation, cytoskeleton structure, metabolic pathways, transcription control, and stress responses, were influenced by maternal age [43]. In this study, no difference in the relative expression levels of the SMC3, SMC1β and STAG3 mRNAs between the groups was observed, and no REC8 mRNA expression was found (Supplementary Data Figure 1), most likely because little or no Cohesin turnover occurs for over 2 weeks during oocyte growth [44].…”
Section: Disscussionmentioning
confidence: 54%
“…It is reported that the expression of oocyte genes that are related to cell cycle regulation, cytoskeleton structure, metabolic pathways, transcription control, and stress responses, were influenced by maternal age [43]. In this study, no difference in the relative expression levels of the SMC3, SMC1β and STAG3 mRNAs between the groups was observed, and no REC8 mRNA expression was found (Supplementary Data Figure 1), most likely because little or no Cohesin turnover occurs for over 2 weeks during oocyte growth [44].…”
Section: Disscussionmentioning
confidence: 54%
“…Additionally, in most organisms, crossing over is essential to ensure accurate segregation of homologous chromosome pairs at the first meiotic division. Cohesin-stabilized chiasmata physically tether homologous chromosomes, contributing to their eventual congression to, and coalignment at the metaphase plate (Hodges et al 2005;Tachibana-Konwalski et al 2010). There, the pair is held in balance by opposing forces: centromere cohesion and chiasmata maintaining attachment on one hand vs. spindle fibers pulling each homolog toward opposite poles.…”
mentioning
confidence: 99%
“…A lack of turnover of the meiotic cohesin protein is considered to contribute to age-related chromosome segregation errors in oocytes. [32][33][34] The molecular mechanisms that maintain or disrupt meiotic cohesion have remained unclear for many decades. However, the candidate genes in cluster 2 in our current study may assist with our understanding of this complex phenomenon going forward.…”
Section: Discussionmentioning
confidence: 99%